Human papillomavirus genotype distribution among Thai women with high-grade cervical intraepithelial lesions and invasive cervical cancer: A literature review - Chumnan Kietpeerakool (2018)
Infection with high-risk human papillomavirus (HR-HPV) is an essential cause of cervical cancer. Because of substantial geographical variation in the HPV genotype distribution, data regarding HPV type-specific prevalence for a particular country are mandatory for providing baseline information to estimate effectiveness of currently implemented HPV-based cervical cancer prevention. Accordingly, this review was conducted to evaluate the HR-HPV genotype distribution among Thai women with precancerous cervical lesions i.e. cervical intraepithelial neoplasia grade 2-3 (CIN 2-3), adenocarcinoma in situ (AIS), and invasive cervical cancer by reviewing the available literature. The prevalence of HR-HPV infection among Thai women with CIN 2-3 ranged from 64.8% to 90.1% and the three most common genotypes were HPV 16 (38.5%), HPV 58 (20.0%), and HPV 18 (5.5%). There were high squamous cell carcinoma/CIN 2-3 prevalence ratios in women with CIN 2-3 infected with HPV 33 and HPV 58 (1.40 and 1.38, respectively), emphasizing the importance of these subtypes in the risk of progression to invasive cancer among Thai women. Data regarding the prevalence and genotype distribution of HR-HPV in Thai women with AIS remain unavailable. Interesting findings about the distribution of HPV genotype in cervical cancer among Thai women include: (1) a relatively high prevalence of HPV 52 and HPV 58 in invasive squamous cell carcinoma; (2) the prevalence of HPV 18-related adenocarcinoma is almost double thepreviously reported prevalence, and (3) 75% of neuroendocrine carcinomas are HPV18-positive when taking into account both single and multiple infections.